2009
DOI: 10.1111/j.1468-0467.2009.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentials for migration and mobility among oil workers in the russian north

Abstract: . High population mobility, mainly in the form of out‐migration, is a characteristic feature of the post‐Soviet Russian North. As subsidies from the centre were significantly cut, living standards and the number of inhabitants in many Russian peripheries declined considerably. Nevertheless, there are also prospering regions and industry sectors in these parts of Russia, which are often related to and dependent on the exploitation of natural resources. After introducing general Soviet and post‐Soviet mobility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(37 reference statements)
0
3
0
3
Order By: Relevance
“…Persons inhabiting peripheral areas have a sense of being separated from their country's mainstream life and want to leave their "isolated territory" and "isolated community". In addition, they are perceived by the authorities as a "problem" and even "human burden" (Wein, 1999;Thompson, 2004;Spies, 2009). Declining population figures were also seen by cities of the Southern Urals (irrespective of their size), what, as may be expected, is linked to their economic decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons inhabiting peripheral areas have a sense of being separated from their country's mainstream life and want to leave their "isolated territory" and "isolated community". In addition, they are perceived by the authorities as a "problem" and even "human burden" (Wein, 1999;Thompson, 2004;Spies, 2009). Declining population figures were also seen by cities of the Southern Urals (irrespective of their size), what, as may be expected, is linked to their economic decline.…”
Section: Discussionmentioning
confidence: 99%
“…Limiting the operations, or in the worst-case scenario, liquidation of such an employer caused significant outflows of population, mainly that of working age, and an actual fall of the city (Maslova, 2011). Population outflows are caused mainly by economic decline (large unemployment following liquidation of non-viable enterprises, relatively high maintenance costs and deteriorating infrastructure), intensified by peripheral location and the resultant economic (Wites, 2007) and social impacts (Wein, 1999;Thompson, 2004;Spies, 2009). The greatest population growth in the category was seen by cities having an advantageous location relative to the state border and growth poles (Vysotsk in the Leningrad Oblast -33.9%, a major sea port, Ladushkin in the Leningrad Oblast -21.8%; Kamenogorsk in the Leningrad Oblast, foreign investments, railway line modernisation for goods transport to Finland) or lying in oil and natural gas producing areas (Kedrovy in the Tomsk Oblast -22.7%).…”
Section: Population Change By City Sizementioning
confidence: 99%
“…In an early review, Wegren and Drury (2001, p. 15) wrote that 'relatively little attention has been devoted in the academic literature to internal migration flows or their potential impact on transitional Russia.' More recent work has addressed internal migration with respect to employment fields or geographic regions (Eldarov et al 2007, Spies 2009). There is a growing consensus that internal migration is important to the Russian economy; Wegren and Drury (2001) reported that in the mid-1990s, 80% of all Russian migration was internal.…”
Section: Migration In the Former Soviet Unionmentioning
confidence: 99%
“…lokalizacja miejsca zamieszkania w ujęciu centrum-peryferie, miasto-wieś, dostępność do infrastruktury społecznej; peryferyjność przyczynia się do utrudnienia kontaktów międzyludzkich z instytucjami i grupami społeczeństwa zarówno położonymi w centrum danego państwa, jak i przedstawicielami społeczeństwa globalnego. Osoby zamieszkujące obszary peryferyjne mają poczucie odizolowania od głównego nurtu życia kraju i wykazują chęć opuszczenia "izolowanego terytorium" i "izolowanego społeczeństwa"; dodatkowo postrzegani są przez władze jako "problem", a nawet "ludzki balast" (Wein 1999;Thompson 2004;Spies 2009); (4) administracyjnych, np. likwidacja ograniczeń formalnych hamujących mobilność ludności (Wein 1999); (5) historycznych, tj.…”
Section: Wprowadzenieunclassified
“…decyzje podejmowane w okresie gospodarki centralnie planowanej i zagospodarowywaniu obszarów peryferyjnych (m.in. Heleniak 2003;Spies 2009); (6) środowiskowych (tj. jakości środowiska) -dotyczy to tych miast i obszarów, które obecnie są poddane silnej antropopresji (np.…”
Section: Wprowadzenieunclassified